Genetic vulnerabilities to prenatal alcohol exposure: Limb defects in sonic hedgehog and GLI2 heterozygous mice. Issue 11 (15th May 2017) - Fish, Eric W.; Murdaugh, Laura B.; Sulik, Kathleen K.; Williams, Kevin P.; Parnell, Scott E.
Abstract : Background: Genetic factors influence the physical and neurobehavioral manifestations of prenatal alcohol exposure (PAE). Animal models allow the investigation of specific genes that confer vulnerability to, or protection from, birth defects associated with fetal alcohol spectrum disorders (FASDs). The objective of the present experiments was to determine if genetic alterations in the Sonic Hedgehog (Shh) signaling pathways affect the vulnerability to PAE‐induced skeletal defects involving the forelimbs and/or hindlimbs. Method: Wild‐type C57BL/6J female mice were bred with males in which one copy of the Shh or Gli2 genes had been knocked out, to produce litters with both wild‐type ( +/+ ) and heterozygous ( +/− ) embryos. Alcohol doses (two injections of 2.9 g/kg, 4 hours apart) or vehicles were administered starting at gestational day (GD) 9.25, 9.5, or 9.75, a critical exposure time for inducing limb defects. Limb defects were examined at GD 17 using a dysmorphology scale based on abnormalities ranging from increased interdigital spacing to the deletion of multiple fingers and the ulna. Results: Alcohol treatment caused a high incidence of forelimb defects, particularly on the right side, that was higher in Shh +/− and Gli2 +/− fetuses compared to wild‐type fetuses. Dysmorphology scores were also significantly higher in the Shh +/− and Gli2 +/− mice. Conclusions: These results extend previous findings demonstrating enhanced sensitivity to PAE‐induced craniofacial dysmorphology and support the hypothesis that genetic alterations in the Shh signaling pathway influences the vulnerability to alcohol‐induced birth defects. Moreover, these results emphasize the importance of understanding the interactions between genes and prenatal exposure to alcohol or other teratogens. Birth Defects Research 109:860–865, 2017. © 2017 Wiley Periodicals, Inc.